Handbook of research on sustaining SMEs and entrepreneurial innovation in the post-COVID-19 era - Baporikar, Neeta (Advances in business strategy and competitive advantage., 2021)
"This edited book deals with the continuing emphasis being placed on SMEs and Entrepreneurship, innovation, and sustainability globally especially now with the post-pandemic business atmosphere in both developed and developing economies"--